2020
DOI: 10.1002/pol.20200470
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stimulated depolarization current spectra of cross‐linked polyethylene and the influence of cross‐linking byproducts

Abstract: Cross-linked polyethylene (XLPE) is notable for its use as power cable insulation. Its longevity is limited by space charge buildup linked to impurities such as the byproducts left behind by the cross-linking agent dicumyl peroxide (DCP). The goal of this work is to determine the impacts of these byproducts on charge trapping and detrapping in XLPE using the thermally stimulated depolarization current technique. XLPE with byproducts has one source of trapped charge, which originates from the byproducts. XLPE t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Meanwhile, the surface effect generated by the addition of BNNSs causes interfacial polarization between the composite and the test interface, thus leading to the increase of the relative dielectric constant of the composites. In addition, when the sample is vulcanized, the thermal decomposition of the vulcanizing agent Dicumyl Peroxide (DCP) produces cross-linking byproducts such as cumyl alcohol, acetophenone, etc [32,33] . The polar groups carried by these byproducts increase the dipole moment of the EPDM molecule, which increases the dielectric constant of the molecule.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…Meanwhile, the surface effect generated by the addition of BNNSs causes interfacial polarization between the composite and the test interface, thus leading to the increase of the relative dielectric constant of the composites. In addition, when the sample is vulcanized, the thermal decomposition of the vulcanizing agent Dicumyl Peroxide (DCP) produces cross-linking byproducts such as cumyl alcohol, acetophenone, etc [32,33] . The polar groups carried by these byproducts increase the dipole moment of the EPDM molecule, which increases the dielectric constant of the molecule.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…Instead, there was a clustering of the activation energy values around 0.15 eV and preexponential factor around 10 -10 S m -1 in AC measurement. These samples would retain significant amounts of DCP byproducts such as acetophenone, which produces space charge in the presence of water and cumyl alochol, which would decompose into water and methylstyrene [28]. While it has been reported that water addition will enhance the conductivity and decrease the activation energy [3,[29][30][31] and influence the preexponential factor [29,30] of polymers such as polyethylene, the presence of these chemical byproducts and their interaction with water must also be considered.…”
Section: Comparison Of DC and Acmentioning
confidence: 99%
“…As shown in Figure 4a-c, acetophenone was found in all three types of cable. Acetophenone is commonly used as a plasticizer or component of ink [20,21]. It probably originates from the inkjet printing on the cables.…”
Section: Compositional Analysis Of Gases Generated From Overheated Cablesmentioning
confidence: 99%